Associations of overweight and gestational diabetes mellitus with free sugars from solid and liquid sources: cross-sectional and nested case-control analyses - Joseph Mussa; Anne-Sophie Brazeau; Tricia Peters; Mourad Dahhou; Claudia Sanmartin; Nancy Ross; Elham Rahme; Kaberi Dasgupta (BMC, 2021)
Abstract Background Sugar-sweetened beverages have obesogenic and diabetogenic effects ascribed to free sugars. These include added sugars and naturally occurring sugars in juices. A meta-analysis indicates that some foods with added sugars are associated with lower type 2 diabetes rates. To expand the evidence relevant to free sugars from solid sources, we examined a young to middle-aged population with respect to overweight and gestational diabetes (GDM) outcomes. Methods We studied female participants (12-50 years old) from the 2004-2005 Canadian Community Health Survey 2.2 (CCHS) with data linked to the hospital Discharge Abstract Database (DAD) until 2017, providing 13 years of follow-up. We estimated free sugars by solid and liquid sources from 24-h dietary recalls as percent total energy intake (TE%), and computed body mass index (BMI). We applied ICD-10 diagnostic codes for deliveries and GDM to DAD. We conducted multivariable logistic regression analyses to evaluate associations between free sugars with overweight at baseline (cross-sectional component) and, in those who delivered, with GDM during follow-up (nested case control component). We compared those with consumption above versus below various thresholds of intake for free sugars, considering solid and liquid sources separately (2.TE%, 5TE%, 10TE% and 15TE% thresholds). Results Among 6305 participants, 2505 (40%) were overweight, defined as BMI ≥ 85th percentile below 18 years and BMI ≥ 25 kg/m2 for adults. Free sugars from solid sources were associated with lower odds of overweight above versus below the 2.5TE% (adjusted odds ratio [adjOR] 0.80, 95%CI 0.70-0.92), 5TE% (adjOR 0.89, 95%CI 0.79-0.99), and 10TE% (adjOR 0.86, 95%CI 0.75-0.97) thresholds. Free sugars from liquid sources were associated with greater odds of overweight across the 2.5TE% (adjOR 1.20, 95%CI 1.07-1.36), 10TE% (adjOR 1.17, 95%CI 1.02-1.34), and 15TE% (adjOR 1.43, 95%CI 1.23-1.67) thresholds. There were 113 cases of GDM among the 1842 women who delivered (6.1%). Free sugars from solid sources were associated with lower odds of GDM above versus below the 5TE% threshold (adjOR 0.56, 95%CI 0.36-0.85). Conclusions Our findings support limiting free sugars from liquid sources, given associations with overweight. We did not identify adverse associations of free sugars from solid sources across any of the thresholds examined.